Histochemical and Immunohistochemical Methods for the Identification of Proteoglycans - Godoy-Guzman, C (Humana Press Inc., 2023)
Proteoglycans (PGs) are non-fibrillar extracellular matrix (ECM) molecules composed by a protein core and glycosaminoglycan (GAG) chains. These molecules are present in all tissues playing essential structural, biomechanical, and biological roles. In addition, PGs can regulate cell behavior due to their versatility and ability to interact with other ECM molecules, growth factors, and cells. The distribution of PGs can be evaluated by histochemical and immunohistochemical methods. Histochemical methods aimed to provide a useful overview of the presence and distribution pattern of certain groups of PGs. In contrast, immunohistochemical procedures aimed the identification of highly specific target molecules. In this chapter we described Alcian Blue, Safranin O, and Toluidine Blue histochemical methods for the screening of PGs in tissue sections. Finally, we describe the immunohistochemical procedures for specific identification of PGs (decorin, biglycan, and versican) in formaldehyde-fixed and paraffin-embedded tissues. © 2023, The Author(s), under exclusive license to Springer Science+Business Media, LLC, part of Springer Nature.